SPEECH ACTS IN ENGLISH LEARNING CLASSROOMS (Case Study at The Islamic College Jakarta) - Fitriyah Fitriyah (Universitas Islam Sumatera Utara (UISU), 2021)
This study aims to analyze and describe (1) the form of speech acts in interactions in the English learning class at Islamic College Jakarta and (2) the types of speech acts in the interaction in the English class at Islamic College Jakarta. To achieve this goal, the researcher used a descriptive qualitative research design. The subjects of this study were students of Islamic College Jakarta. The objects in this study are the form, function, and type of speech uttered by Islamic College Jakarta students in the interaction of learning English in the classroom. Data collection and research using the note-taking method assisted by recording techniques. Data analysis in this study used qualitative data analysis procedures based on the interactive Miles model which generally includes three stages, namely (1) data reduction, (2) data presentation, (3) verification. The results of this study indicate that: (1) The form of speech acts of students in the English class, namely the form of speech acts in the declarative mode, the interrogative mode, and the imperative mode. (2) Types of speech acts of students in English class, direct literal speech acts, non-literal direct speech acts, literal indirect speech acts, and non-literal indirect speech acts. The use of direct speech acts aims to make speech partners easier to understand what the speakers (lecturers or students) want. Suggestions that can be given through this research are for lecturers, students, other researchers, and readers, this research can be used as a guideline, reference, and comparison material to gain insight into the field of linguistic science, especially speech acts.